IMPLIKASI DOKTRIN “FAIR USE” TERHADAP PENGEMBANGAN ILMU PENGETAHUAN OLEH AKADEMISI (DOSEN) ATAU PENELITI DALAM PERSPEKTIF HUKUM HAK CIPTA - Sudjana, Sudjana (Faculty of Law, Parahyangan Catholic University, 2018)
In this article the author discusses the fair use (Art. 43-49 Law 28/2014 re. copyright) in relation scientific work performed by lecturers and researchers. This legal discourse in the field of copyright law will be performed using a juridical normative approach. One important finding is that the fair use doctrine allows lecturers and researchers to utilize copyright protected work from others – in the name of scientific progress or educational purposes – without having to obtain prior consent or license. Nonetheless, user of copyright protected works must pay attention to reasonable interest of copyright holder, the meaning of which is left to legal practice.